Preconceito e trauma no processo migratório dekassegui - Maejima, Adriana Tie (2013)
This research had as its object of study, the migratory phenomenon Dekassegui with the focus of analysis of Prejudice and Trauma. The goal was to identify and understand the unconscious motivations of these immigrants who migrated to Japan and study some historical-cultural aspects that led to the Japanese membership of most individuals to migration. The theoretical approach chosen for this literature review was to Psychoanalytic Theory and the Critical Theory of Society. To complete this research, the study of myths of Japan and Japanese psychoanalysts who beheld training psychic different from Western, favored the understanding of the phenomenon of psychic transmission of trauma and repeated experience with prejudice.